VIRTUAL FLIPPED CLASSROOM FOR DEVELOPING EFL STUDENTS SPEAKING SKILLS: DESIGN AND IMPLEMENTATION - Baskara, Risang (International Journal of Humanity Studies (IJHS), 2024)
In Indonesia, English as a Foreign Language (EFL) students often struggle with developing speaking skills due to limited classroom time and cultural tendencies towards passive learning. This study investigated the effectiveness of a virtual flipped classroom in addressing these challenges and enhancing EFL students' speaking abilities. The research involved 40 Indonesian university students, divided equally into experimental and control groups. The experimental group participated in a virtual flipped classroom, completing pre-class online activities and engaging in in-class speaking exercises, while the control group received traditional instruction. Pre- and post-tests assessed speaking skills, supplemented by student surveys. Results revealed significantly higher post-test scores in the experimental group compared to the control group. Furthermore, survey data indicated that students perceived the virtual flipped classroom as effective in promoting active learning and enhancing their speaking skills. This approach shows promise in overcoming cultural barriers to active participation and maximizing limited class time for speaking practice in Indonesian EFL contexts. However, further research is needed to explore long-term effects and optimal implementation strategies across diverse EFL settings.